The Porthmion Archaeological Expedition of the Institute for the History of Material Culture (IHMC RAS) - Vakhtina, Marina Ju. (Hyperboreus, 2006)
A survey of the excavations in Porthmion conducted by the Institute for the History of Material Culture.